2015
DOI: 10.1128/genomea.00971-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Bacillus licheniformis S127, Isolated from a Sheep Udder Clinical Infection

Abstract: Bacillus licheniformis is a Gram-positive biofilm-and endospore-forming bacterium, which contaminates dairy products and can be pathogenic to humans. The draft genome sequencing for B. licheniformis strain S127 is reported here, providing genetic data relevant to the ability of this strain to sustain its survival in the dairy industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The most common Bacillus species found in dairy associated environment are B. licheniformis , B. cereus , B . subtilis , B. mycoides and B. megaterium ( Andersson et al, 1995 ; Bartoszewicz et al, 2008 ; De Jonghe et al, 2008 ; Ledenbach and Marshall, 2009 ; Ostrov et al, 2015 ). It was previously shown that the majority of isolates from raw milk from organic and conventional dairy farms belonged to the genus Bacillus and showed at least 97% 16S rRNA gene sequence similarity with type strains of B. licheniformis , B. pumilus , B. circulans , B. subtilis and B. cereus ( Coorevits et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common Bacillus species found in dairy associated environment are B. licheniformis , B. cereus , B . subtilis , B. mycoides and B. megaterium ( Andersson et al, 1995 ; Bartoszewicz et al, 2008 ; De Jonghe et al, 2008 ; Ledenbach and Marshall, 2009 ; Ostrov et al, 2015 ). It was previously shown that the majority of isolates from raw milk from organic and conventional dairy farms belonged to the genus Bacillus and showed at least 97% 16S rRNA gene sequence similarity with type strains of B. licheniformis , B. pumilus , B. circulans , B. subtilis and B. cereus ( Coorevits et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Strains belonging to the B. subtilis and B. cereus groups were shown to be strongly proteolytic ( Lücking et al, 2013 ). Interestingly, Bacillus strains including B. cereus ( Wijman et al, 2007 ), B. licheniformis ( Hoong et al, 2012 ; Ostrov et al, 2015 ) and B. subtilis ( Bridier et al, 2011 ) are able to form submerged surface-associated biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…The following bacterial strains were used in this study: (i) dairy-associated isolates, such as B. paralicheniformis S127 [24,25], B. licheniformis MS310, B. subtilis MS302, B. paralicheniformis MS303 [24]; (ii) non-dairy isolate B. subtilis NCIB3610 (descendant of B. subtilis Marburg); (iii) poly-γ-glutamic acid (PGA)-overproducing mutant derivatives of B. subtilis 3610, B. subtilis YC295 (Δ ywcC ) and B. subtilis YY54 (Δ pgdS ) (a gift of Y. Chai [18]). B. licheniformis MS310, B. subtilis MS302 and B. paralicheniformis MS303 whole-genome shotgun projects are deposited at DDBJ/EMBL/GenBank, under accession numbers MIPQ00000000, MIZD00000000, MIZE00000000 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they are the predominant type of gram‐positive bacteria isolated from both raw and pasteurized milk, pre‐ and post‐pasteurization segments of dairy plants . The most common Bacillus species found in dairy‐associated environments are B. licheniformis , B. cereus , B. subtilis , B. thuringiensis , B. weihenstephanensis, B. mycoides, B. sporothermodurans , and B. megaterium …”
Section: Persistence Of Biofilm Formed By Bacillus Species In the Daimentioning
confidence: 99%
“…36,43,48 The most common Bacillus species found in dairy-associated environments are B. licheniformis, B. cereus, B. subtilis, B. thuringiensis, B. weihenstephanensis, B. mycoides, B. sporothermodurans, and B. megaterium. [49][50][51] The ability to adhere to surfaces and form biofilms enables Bacillus species to thrive in the dairy-associated environment, as it facilitates their dispersion and survivability. 28,35 Thus, milkderived Bacillus strains should be characterized by the formation of robust submerged biofilm during growth in milk.…”
Section: Persistence Of Biofilm Formed By Bacillus Species In the Daimentioning
confidence: 99%